2016
DOI: 10.1159/000450825
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Carvedilol on Cardiac Function and the AKT/XIAP Signaling Pathway in Diabetic Cardiomyopathy Rats

Abstract: Objectives: Diabetic cardiomyopathy (DCM) is characterized by cardiac dysfunction, myocardial inflammation, interstitial fibrosis and cardiomyocytes apoptosis. The present study aimed to investigate the effects of carvedilol on cardiac function and the AKT/XIAP signaling pathway in DCM rats. Methods: Male Wistar rats were randomly divided into 3 groups: the control group, diabetic mellitus (DM) group and DM with carvedilol treatment group. DM rats were induced by streptozotocin accompanied by high energy intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
3
4
0
1
Order By: Relevance
“…The results of the present study demonstrated that IA could inhibit the antiapoptotic mechanism of the cells through the regulation of expression of various proteins, and the results were consistent with previous studies (35,40,41) of the PI3K/Akt/xIAP pathway. The present results highlight a potential candidate compound for the management of prostate cancer and provide a theoretical basis for the pathogenesis of prostate cancer.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study demonstrated that IA could inhibit the antiapoptotic mechanism of the cells through the regulation of expression of various proteins, and the results were consistent with previous studies (35,40,41) of the PI3K/Akt/xIAP pathway. The present results highlight a potential candidate compound for the management of prostate cancer and provide a theoretical basis for the pathogenesis of prostate cancer.…”
Section: Discussionsupporting
confidence: 93%
“…The authors concluded that they were associated and involved in the pathogenesis of diabetic cardiomyopathy. The effect of carvedilol in control animals was not investigated in this study and the authors have not linked their findings with GPCR coupling or biased agonist activity of carvedilol (Zheng et al, 2017(Zheng et al, , 2019.…”
Section: Discussionmentioning
confidence: 96%
“…Akt exhibits distinct key roles in regulating cardiovascular functions, such as blood pressure, regulation of myocardial systolic and diastolic functions, coronary angiogenesis and atherosclerosis (37). GSK-3β is the major substrate of the Akt-GSK-3β pathway that exerts specific physiological and biochemical functions in glycogen metabolism and plays a decisive role in diabetes-induced inflammation and fibrosis (38). Previous investigations have demonstrated that the Akt-GSK-3β signaling pathway plays an important function in diabetes-induced energy metabolic dysfunction and consequently in heart hypertrophy (39,40).…”
Section: Discussionmentioning
confidence: 99%